Perceptions and clinical practice around use of airway clearance devices in chronic obstructive pulmonary disease: a cross-sectional survey of respiratory care and physiotherapy practitioners in Saudi Arabia - Alzahrani, Ahmed; Alghamdi, Saeed; Majrshi, Mansour; Alasmari, Ali; Alshehri, Ziyad; Alahmadi, Fahad; Al Qahtani, Sultan; Alhawsawi, Abdulrahman; Alasimi, Ahmed; Eilayyan, Owis; Polkey, Michael; Birring, Surinder; et al. (J Med Rehab Sci, 2025)
Background: Effective airway clearance is a critical component of COPD management. Airway clearance devices (ACDs) can assist this, but their effectiveness relies on consistent use in clinical practice. Objectives: To identify awareness and clinical practice related to device use for people with COPD among respiratory therapists and physiotherapists in Saudi Arabia. Design: A cross-sectional survey. Setting: Primary and secondary care in Saudi Arabia Material and Methods: An online survey was conducted among respiratory care and physiotherapy practitioners working in various healthcare settings across Saudi Arabia. The survey assessed familiarity with, attitudes towards, and utilisation of different types of ACDs in different clinical scenarios. Results: A total of 423 healthcare practitioners were invited to complete the survey, which included 43% female participants, a median age range of 20-30 years, 89.4% Saudi citizens, 82.5% with a bachelor’s degree, 84.2% who are respiratory therapists, and 58.9% employed in governmental hospitals. Almost all participants were aware of at least one ACD, with Flutter devices (58%) being the most recognised, followed by Acapella (30%). 77.5% of participants reported always or usually using devices in patients with daily difficulty in clearing thick sputum, but there was less consistency where the sputum burden was not as severe. The Acapella device was preferred by 56%, with 18% preferring the Flutter. 85% of participants reported basing device use on clinical practice guidelines, with the GOLD guidelines being the most cited. Conclusion: Awareness of sputum clearance devices is high among this group of healthcare professionals in Saudi Arabia, but variation in practice highlights the need for further research. Keywords: Chronic Obstructive Pulmonary Disease, Airway Clearance Devices, Adjunct for Sputum Clearance, Respiratory Therapy, Physiotherapy, Saudi Arabia